Thromboprophylaxis practice patterns in two Western Australian teaching hospitals - JW Eikelboom; A Mazzarol; DJ Quinlan; R Beaver; J Williamson; Q Yi; GJ Hankey; The American College of Chest Physicians (Haematologica, 2004)
BACKGROUND AND OBJECTIVES: Evidence-based international guidelines recommend that all patients undergoing elective hip or knee arthroplasty receive thromboprophylaxis with low-molecular-weight heparin or adjusted-dose warfarin. Our objective was to determine what proportion of patients undergoing elective hip or knee arthroplasty actually receive recommended thromboprophylaxis according to international guidelines. DESIGN AND METHODS: We performed a prospective cohort study of 396 consecutive patients undergoing elective hip or knee arthroplasty between 1 May and 30 October, 2002. We collected baseline data, surgical and anesthetic details and recorded use of thromboprophylaxis and episodes of venous thromboembolism that occurred within 3 months of surgery. RESULTS: The mean age of the patients was 69.4 years (SD 11.5 years), and 62.2% (95% CI: 57.3 to 66.9%) were female. Hip arthroplasty was performed in 39.4% (34.6 to 44.2%) and knee arthroplasty in 57.1% (52.2 to 61.9%). Recommended thromboprophylaxis with low-molecular-weight heparin or warfarin was administered to 51.5% (46.6 to 56.4%). Objectively diagnosed venous thromboembolism occurred in 5.3% (3.3 to 8.0%) of patients; 3.5% (1.9 to 5.9%) of events occurred during hospitalization and 1.8% (0.7 to 3.6%) occurred following discharge from hospital. There was no significant reduction in the incidence of venous thromboembolism among patients treated with recommended thromboprophylaxis compared with those who did not but this is not a randomized comparison and is potentially confounded by the indication for treatment. INTERPRETATION AND CONCLUSIONS: Current thromboprophylaxis practice at our institutions falls substantially short of national and international guidelines. The reasons for low thromboprophylaxis use should be further explored and strategies for change implemented in order to optimize clinical practice.